(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Evidence-informed policymaking is a current area of development within public administration. This study investigates the utilisation of evidence in the physical activity policy work of the Finnish Parliament’s Education and Culture Committee. Methods: The research explores expert opinions submitted to the Education and Culture Committee, alongside the reports and statements issued by the Committee. The dataset comprises 70 expert opinions on physical activity policy, along with 10 reports and statements authored by the Committee. Quantitative content analysis was conducted and supplemented with qualitative methods. Results: Findings reveal that the vast majority of the arguments in expert opinions were presented as ‘general knowledge’, with no explicit indication of their source, implying they were universally accepted facts. However, such information often appeared to stem from specific sources, such as research, surveys, or assessments. Only a minor proportion of arguments in the expert opinions were based on research evidence. Similar patterns were identified within the Committee’s reports and statements. Many of the arguments presented in the Committee’s reports and statements originated from expert opinions. It varied as to whether these arguments were presented as ‘general knowledge’ or explicitly stated to be ‘sourced from expert opinions’. Conclusion: The reliance on ‘general knowledge’ in expert opinions presents challenges for policymakers. This lack of transparency makes it difficult to identify the origin of the knowledge or evaluate its reliability. The predominance of unsubstantiated general knowledge undermines the implementation of evidence-informed policymaking and may diminish its impact. Support/Funding Source: This research was conducted without external funding.